Gagasan Islam Progresif Abdurrahman Wahid dan Relevansinya dengan Kemunculan Negara Islam Indonesia (NII) di Minangkabau - Fererli, Delavia Andrea; Ramadan, Risky Aulya (Media: Jurnal Filsafat dan Teologi, 2025)
This study aims to explain Abdurrahman Wahid’s (Gus Dur’s) progressive Islamic ideas and their relevance to the emergence of the terrorist network group Negara Islam Indonesia (NII) in Minangkabau. Using a qualitative approach through library and field research, data were collected via observation, interviews, and document analysis, drawing primarily from Gus Dur’s Islamku, Islam Anda, Islam Kita and related literature. The analysis employed data reduction, data presentation, and conclusion drawing. The results show that Gus Dur rejected the formalization, ideologization, and shariatisation of Islam in state affairs, emphasizing that Islam’s strength lies in its ethical and cultural values rather than institutional political forms. His concept of  Islamic indigenization served as a reconciliation between Islamic teachings and local wisdom, while his reform of Islamic jurisprudence, based on maqāṣid al-syarī‘ah, underscored justice, humanity, and freedom. The study concludes that Gus Dur’s progressive Islamic thought remains highly relevant in addressing radical ideologies in Minangkabau. His legacy of pluralism, tolerance, and humanism offers a foundational framework for fostering peaceful and democratic religious life in Indonesia.